Leadership Commitment to Building an Organizational Culture to Improve Employee Performance at The National Police Commission (Kompolnas) Secretariat - Joko Purwanto; Harries Madiistriyatno; Nurwulan Kusumadewi (Dinasti Publisher, 2026)
The purpose of the study is to describe and analyze the influence of leader commitment on employee performance, to find out whether there is an influence of organizational culture on employee performance and to find out whether there is an influence of leader commitment and organizational culture on employee performance of the National Police Commission Secretariat (Kompolnas). The results of the t test show that the calculated t value of 7.425 is greater than the t table value of 1.996 at a significance level of 5%. Based on the results of the t test, the calculated t value is 9.625, which is greater than the t table value of 1.996. The results of the F test show that the calculated F value is 285.298, greater than the F table value of 2.74 with a significance level of 0.000 <0.05. The coefficient of determination (R Square) of 0.901 indicates that 90.1% of employee performance variation is influenced by Leader Commitment and Organizational Culture, while the remaining 9.9% is influenced by other factors not examined in this study, such as work motivation, job satisfaction, competence, work environment, and reward systems.